2022
DOI: 10.1088/1361-648x/ac577b
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for first-principles simulations of epitaxial inorganic interfaces

Abstract: At an interface between two materials physical properties and functionalities may be achieved, which would not exist in either material alone. Epitaxial inorganic interfaces are at the heart of semiconductor, spintronic, and quantum devices. First principles simulations based on density functional theory (DFT) can help elucidate the electronic and magnetic properties of interfaces and relate them to the structure and composition at the atomistic scale. Furthermore, DFT simulations can predict the structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 309 publications
(451 reference statements)
2
13
0
Order By: Relevance
“…We further note a strong dependence of the U values on the BO hyperparameters, as discussed in Ref. [98]. U ef f values used and Bayesian optimization convergence plots are shown in Table S1 and Figure S1, respectively.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…We further note a strong dependence of the U values on the BO hyperparameters, as discussed in Ref. [98]. U ef f values used and Bayesian optimization convergence plots are shown in Table S1 and Figure S1, respectively.…”
Section: Methodssupporting
confidence: 56%
“…47 atomic layers of the semiconductor were used, based on previous band gap convergence studies [29,110,111]. The Heusler thickness was converged with respect to the density of states and magnetic moment, which should approach the bulk limit at the center of the slab [98]. For Ti 2 MnIn, the convergence test was performed with the TiIn termination.…”
Section: Resultsmentioning
confidence: 99%
“…STM simulations were performed using the Tersoff and Hamann approximation, which states that the tunneling current is proportional to the local density of states (LDOS). 31 To generate the pristine 2×2 surface reconstruction, an In-terminated InAs(111) surface was constructed with 40 Å of vacuum, using an InAs lattice parameter of 6.0584 Å. Pseudohydrogen atoms with charges of 0.75 ewere appended to the bottom surface to passivate the dangling bonds that result from cleaving of the surface, 32 and a single In atom was then removed from the top surface. Next, ionic relaxation of the top four atomic layers and the pseudo-hydrogen positions was performed until the Hellman-Feynman forces acting on ions were below 0.001 eV/ Å.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that (semi-)local functionals fail to describe the bulk band structure of α-Sn correctly, specifically the band ordering and the orbital composition of the valence bands at the Γ point. DFT+U, hybrid functionals, or many-body perturbation theory within the GW approximation are necessary to obtain a correct description of the band structure [29,35,[57][58][59]. DFT+U simulations have required slab models of more than 30 monolayers of Sn to converge towards a bulk regime, where quantum confinement is no longer dominant.…”
Section: Introductionmentioning
confidence: 99%